Examining the Roles of Transformational Leadership, Emotional Intelligence, and Work-life Balance in Millennial Employee Engagement - Nugroho J. Setiadi; Harry Sutanto; Nopriadi Saputra; Afifah T. Natatilova; Desta L. Leo; Zaky Al Faridz (Australasian Accounting, Business and Finance Journal, 2024)
Strategically addressing the retention of millennial employees, who are poised to shape the workforce of the future, is of paramount importance. This study aims to provide deeper insights into the influence of work-life balance, transformational leadership, and emotional intelligence on employee engagement, with a specific focus on millennial workers. The research involved 163 millennial employees with a minimum of one year of work experience in Indonesia who participated in an online survey as part of a quantitative approach. The results of data analysis using SPSS 25 reveal that both work-life balance and transformational leadership exert a partial impact on employee engagement, whereas emotional intelligence shows no significant influence. It is evident that employee engagement is influenced by a combination of factors, including work-life balance, transformational leadership, and emotional intelligence, among others.
Keywords: Millennial Generation; work-life balance; Transformational Leadership; Emotional Intelligence; Employee Engagement